A process of defence – securing industrial control systems. Issue 2 (February 2017) - Mansfield-Devine, Steve
Abstract : For people whose job is to secure industrial systems, history can be divided into two epochs – before Stuxnet and after Stuxnet. 1 It seems the US/Israeli attack on Iran's nuclear processing facility was something of a wake-up call, dispelling the sense of complacency that had built up in many industrial sectors. However, as Andrea Carcano, co-founder and chief product officer at Nozomi Networks, explains in this interview, while security has certainly improved, making these systems resilient is a long, gradual process and we're a long way from being where we need to be.